A psychosocial approach to understanding the capacities to care and think critically in student mental health nurses - Dixon, Julie (2019)
The thesis focuses on mental health nurse motivation and education. Both caring behaviours and critical thinking are essential components of being a capable mental health nurse. By positioning student mental health nurses as psychosocial defended subjects, the research reported here shows theoretically and empirically that caring behaviours and critical thinking dispositions are mutually inclusive and both are influenced by dynamic psychosocial factors.